Pelatihan Pengenalan Dasar-Dasar Akuntansi Bagi Siswa SMAN 11 Solok Selatan Untuk Meningkatkan Pemahaman Literasi Akuntansi - Ria Angriani; Tika Arizona; Lasmi Yupita; Ridho Deza Perkasa; Yeni Sofiarna (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service activity aims to improve accounting literacy through basic accounting cycle training for students of SMAN 11 Solok Selatan in grades 10, 11, and 12. This training equips them to manage personal or small business finances and prepares them for university or the workforce. Without a basic understanding of accounting, students are susceptible to recording errors, non-transparent cash management, and a lack of ability to assess the financial health of a business. Initial identification results indicate that over 70% of students have never received formal accounting material. The national curriculum only covers basic economic concepts but does not cover practical financial record-keeping practices applicable to everyday life. Improving accounting understanding among students can also foster awareness of the importance of good financial record-keeping. Students of SMAN 11 Solok Selatan need to improve their accounting literacy to better understand and apply basic accounting concepts, such as financial transactions, financial statement preparation, and financial decision-making based on accounting data. This training is expected to improve the competency of SMAN 11 Solok Selatan students in general and their understanding of accounting specifically.